Strategi Membangun Nation Branding di Era 4.0 Bagi Pelaku UMKM di Kabupaten Serang - Husnah Nur Laela Ermaya; Rahmasari Fahria; Wahyu Ari Andriyanto (E-Coops-Day, 2023)
From the results of observations and interviews conducted by the service team, it shows that there are still a lot of MSME actors who do not understand and the importance of Branding. The neglected branding certainly has a negative impact on MSME products in Serang Regency. The purpose of implementing this training and mentoring is to provide socialization and assist MSME actors in building Nation Branding in the 4.0 era. Optimizing the use of brands must be carried out by MSME actors in the hope that it will increase consumer buying interest and competitive selling prices. In addition, a well-built brand is an investment and is expected to provide benefits for MSMEs in the future. The stages of implementing this community service activity are identifying the problems that occur in partners, namely by using an observation approach by interviewing, providing training and finally providing assistance to MSME actors. The results of this activity show that MSME actors have an understanding and awareness of the importance of building nation branding in the 4.0 era so that they can compete nationally with products produced by other MSME actors.